The role of steroid receptors, peptides and growth factors in the aetiopathogenesis of idiopathic gynecomastia. (16th March 2022) - Singh, Vinay Pal; Das, Liza; Kumar, Parmod; Bal, Amanjit; Gaba, Sunil; Tripathy, Satyaswarup; Dutta, Pinaki
Abstract: Idiopathic gynecomastia is a diagnosis of exclusion. We aimed to evaluate the role of steroids, peptides and growth factors in these patients. Those with bilateral idiopathic gynecomastia ( n  = 29) (Simon's grade IIb or III) who underwent gland excision were evaluated by immunohistochemical techniques using semi‐quantitative grading for oestrogen receptor (ER), progesterone receptor (PR), aromatase, androgen receptor (AR), peptides (IGF‐1, IGF‐2, HER‐2, parathyroid‐hormone related peptide [PTHrP]) and growth factors (EGFR, TGFβ). The cohort comprised 29 patients, with a mean age of 25.3 ± 5.1 years and a mean body mass index of 27.2 ± 2.3 kg/m 2 . Grade IIb gynecomastia was present in 79.1% and moderate‐to‐severe insulin resistance (HOMA‐IR >3) in 53.7% of patients. ER expression was positive in 100% samples, followed by AR (96.5%), aromatase (96.5%) and PR (93.1%). IGF‐1 was expressed in 86.2% of the cohort, IGF2 in 27.5% and HER‐2 in only two samples, with both showing weak immunoexpression. None of the patients had positive expression of EGFR, TGF‐β or PTHrP. There was no association between immunoexpression and gynecomastia grade. This study demonstrates the predominant role of oestrogen, aromatase and insulin resistance in the aetiopathogenesis of idiopathic gynecomastia and implicates the paracrine hyperestrogenic milieu in its causation as circulating hormones were normal.